Firm-specific productivity risk over the business cycle: facts and aggregate implications - Ruediger Bachmann; Christian Bayer (Deutsche Bundesbank, 2009)
Is time-varying firm-level uncertainty a major cause or amplifier of the business cycle? This paper investigates this question in the context of a heterogeneousfirm RBC model with persistent firm-level productivity shocks and lumpy capital adjustment, where cyclical changes in uncertainty correspond naturally to cyclical changes in the cross-sectional dispersion of firm-specific Solow residual innovations. We use a unique German firm-level data set to investigate the extent to which firm-level uncertainty varies over the cycle. This allows us to put empirical discipline on our numerical simulations. We find that, while firm-level uncertainty is indeed countercyclical, it does not fluctuate enough to significantly alter the dynamics of an RBC model with only first moment shocks. The mild changes we do find are mainly caused by a bad news effect: higher uncertainty today predicts lower aggregate Solow residuals tomorrow. This effect dominates the real option value effect of time-varying uncertainty, highlighted in the literature.
Keywords: E20; E22; E30; E32; 330; Ss model; RBC model; lumpy investment; countercyclical risk; aggregate shocks; idiosyncratic shocks; heterogeneous firms; news shocks; uncertainty shocks.; Real Business Cycle; Produktivität; Schock; Konjunktur; Risiko; Innovation; Investition; Theorie; Deutschland